Maternal and perinatal complications according to maternal age: A systematic review and meta‐analysis. Issue 1 (7th February 2022) - Saccone, Gabriele; Gragnano, Elisabetta; Ilardi, Bernadette; Marrone, Vincenzo; Strina, Ida; Venturella, Roberta; Berghella, Vincenzo; Zullo, Fulvio
Abstract: Objective: To evaluate the risk levels for maternal and perinatal complications at > 40, > 45 and > 50 years old compared with younger controls. Methods: Electronic databases were searched from their inception until March 2021. We included studies reporting pregnancy outcome in pregnant women aged 40, 45, and 50 years or older compared with controls at the time of delivery. Case reports and case series were excluded. The primary outcome was the incidence of stillbirth. Meta‐analysis was performed using the random effects model of DerSimonian and Laird, to produce summary treatment effects in terms of relative risk (RR) with 95% confidence interval (CI). Heterogeneity was measured using I 2 (Higgins I 2 ). Subgroup analyses in women older than 45 years and in those older than 50 years were performed. Results: Twenty‐seven studies, including 31 090 631 women, were included in the meta‐analysis. The overall quality of the included studies was moderate to high. Most of the included studies were retrospective cohort studies (21/27), four were population‐based studies, and two were cross‐sectional studies. Women aged ≥40 years had significantly higher risk of stillbirth (RR 2.16, 95% CI 1.86–2.51), perinatal mortality, intrauterine growth restriction, neonatal death, admission to neonatal intensive care unit, pre‐eclampsia, preterm delivery, cesarean delivery, and maternal mortality compared with women younger than 40 years old (RR 3.18, 95% CI 1.68–5.98). The increased risks for maternal mortality were 42.76 and 11.60 for women older than 50 years and for those older than 45 years, respectively, whereas those for stillbirth were 3.72 and 2.32. The risk of stillbirth and cesarean delivery was significantly higher in women >45 years compared with those aged 40–45 years, and in those aged >50 years compared with those aged 45–50 years. The risk of maternal mortality was significantly higher in women aged >50 years compared with those aged 40–45 (RR 60.40, 95% CI 13.28–274.74). Conclusion: The risk of stillbirth, cesarean delivery, and maternal mortality increases with advancing maternal age. The risk ratios for maternal mortality were 3.18, 11.60, and 42.76 in women older than 40, older than 45, and older than 50 years, respectively. These data should be used when women with advanced maternal age are counseled regarding their risk in pregnancy. Systematic Review Registration: The review was registered with the PROSPERO International Prospective Register of Systematic Reviews (registration No.: CRD42020208788). Abstract : The risk ratios for maternal mortality were 3.18, 11.60, and 42.76 in women 40 years, 45 years, 50 years, respectively.